DETERMINING THE BURIAL TIME OF SINGLE GRAINS OF QUARTZ USING OPTICALLY STIMULATED LUMINESCENCE - Murray A.S.; Roberts R.G. (My University, 1997)
In the optical dating of sediments it is usually assumed that the optically stimulated luminescence (OSL) signal has been completely reset by light exposure prior to burial; this assumption is often not valid. One approach to testing, and perhaps circumventing, this assumption is to examine the apparent date of last exposure to daylight of individual sediment grains. This paper reports on the application, for the first time, of 2 new measurement protocols to the estimation of the radiation dose received during burial for individual quartz grains from an aeolian deposit of known age (10,000 year old), which is considered likely to have been completely reset by sunlight at deposition. Additive-dose (laboratory doses added to the burial dose before OSL measurement) and regenerative-dose (doses added after measurement of OSL from burial dose) single-aliquot protocols are applied to 28 and 25 individual grains, respectively; each grain provides an independent estimate (De) of the burial dose. The average De from the additive-dose protocol (21.8+/-1.1 Gy) is in good agreement with the average from the regenerative-dose protocol (23.8+/-1.0 Gy). Both agree well with: (1) 13 multiple-grain regenerative-dose single-aliquot measurements, each on 1 mg sub-samples, of 23.9+/-0.3 Gy; (2) 9 multiple-grain additive-dose single-aliquot measurements, also on 1 mg sub-samples, of 22.4+/-0.7 Gy; and (3) one previously published multiple-aliquot additive-dose estimate of 23.5+/-0.6 Gy using 52 sub-samples, each of 5 mg. The resulting optical ages are in good accord with 14C and thermoluminescence age determinations. The distribution of equivalent doses in the single grains is, however, unexpectedly large (σ~23% of mean De), given the very likely complete resetting of the OSL signal at deposition. Possible reasons are discussed, and it is concluded that heterogeneity in beta dosimetry is the most likely explanation. The single-grain optical dating protocols reported here allow a detailed examination of the dose distribution in very small samples. Thus, they should enable accurate dates to be obtained for sediments and soils that contain poorly bleached or mixed-age components, as well as deposits in which quartz grains are present in extremely low abundance.
Keywords: LUMINESCENCE; EOLIANITE; QUARTZ; GRAINS